Blood pressure management in acute stroke - Appleton, Jason P.; Sprigg, Nikola; Bath, Philip M.W. (BMJ, 2016)
Blood pressure (BP) is elevated in 75% or more of patients with acute stroke and is associated with poor outcomes. Whether to modulate BP in acute stroke has long been debated. With the loss of normal cerebral autoregulation, theoretical concerns are twofold: high BP can lead to cerebral oedema, haematoma expansion or haemorrhagic transformation; and low BP can lead to increased cerebral infarction or perihaematomal ischaemia. Published evidence from multiple large, high-quality, randomised trials is increasing our understanding of this challenging area, such that BP lowering is recommended in acute intracerebral haemorrhage and is safe in ischaemic stroke. Here we review the evidence for BP modulation in acute stroke, discuss the issues raised and look to on-going and future research to identify patient subgroups who are most likely to benefit.